International and regional standards of human rights applicable to mental health repair of victims in armed conflict contexts - Chávez Filinich, Tatiana Myrlenko (2019)
In contexts of non-international armed conflicts, victims have been impacted on their psyche or social fabric, affecting them intimately and altering their environment. The situation is aggravated when the victim’s situation is complex: it belongs to some vulnerable group, where gender, ethnicity, religion, socioeconomic stratum, etc. are attended. The right to mental health is enforceable from international human rights law; however, it often lacks the resources and adequate and sufficient management by States. In this article, some of the standards set by the courts on human rights in cases of armed conflict will be reviewed. Specifically: (i) standards issued by agencies and institutions specializing in mental health and, (ii) mental health reparations provided for by courts. There will be also a clear development of progressive jurisprudence.